Rectal Misoprostol versus Intramuscular Oxytocin for Prevention of Post Partum Hemorrhage - Shrestha, A; Dongol, A; Chawla, C D; Adhikari, R (Kathmandu University Medical Journal, 2012)
Background Postpartum hemorrhage (PPH) is an important cause of maternal morbidity and mortality especially in the developing countries. Compared to expectant management, active management decreases the incidence of PPH. Objective To compare the effectiveness of rectal misoprostol with intramuscular oxytocin in the prevention of postpartum hemorrhage. Methods This is a prospective, randomized and analytical study from 1stSeptember 2009 to 28th February 2010 at Department of Obstetrics and Gynecology, Dhulkhel Hospital - Kathmandu University Hospital, Dhulikhel, Nepal. A total of 200 women were included to receive either 1000 micrograms rectal misoprostol tablets or 10 units of oxytocin intramuscularly. Primary outcome measures were the incidence of postpartum hemorrhage or a change in hematocrit or hemoglobin from admission to day two post delivery. Secondary outcome measures including severe postpartum hemorrhage and the duration of the third stage of labor were noted. Also the side effects of both misoprostol and oxytocin were recorded. Results The frequency of postpartum hemorrhage was 4% in the misoprostol subjects and 6% in the control subjects (P=0.886) There were no significant difference among the groups in the drop of hematocrit (P>0.05). Secondary outcome measures including severe postpartum hemorrhage and the duration of the third stage of labor were similar in both groups. Similarly, the side effects between the misoprostol and oxytocin group within 6 hours was statistically significant (p=0.003) whereas the side effects within 24hours was statistically not significant (p=0.106). Conclusion Rectal misoprostol is as effective as intravenous oxytocin in preventing postpartum hemorrhage with the similar incidence of side effects and is worthwhile to be used as a uterotonic agent for the routine management of third stage of labor. http://dx.doi.org/10.3126/kumj.v9i1.6254 Kathmandu Univ Med J 2011;9(1):8-12